Thrombolysis and adjunct anticoagulation in patients with acute basilar artery occlusion. (12th September 2018) - Ritvonen, J.; Strbian, D.; Silvennoinen, H.; Virtanen, P.; Salonen, O.; Lindsberg, P. J.; Sairanen, T.
Abstract : Background and purpose: Patients suffering from basilar artery occlusion (BAO) and treated with intravenous thrombolysis are, in some centers, started on adjunct anticoagulation in hyperacute settings. We aimed to assess the outcome of such patients and to compare low‐molecular weight heparin (LMWH) and unfractionated heparin (UFH) in this context. Methods: We examined 211 patients with angiography‐proven BAO treated with intravenous thrombolysis and either adjunct UFH or LMWH. Main outcome variables were rate of symptomatic intracranial hemorrhage (sICH) according to European Cooperative Acute Stroke Study II criteria and modified Rankin Scale (mRS) at 3 months. Results: The overall rate of sICH was 11.4% and driven by the UFH group (13.3%). None of the LMWH group developed sICH. Recanalization rate did not significantly differ between the LMWH and UFH groups. An additional propensity analysis was made to balance anticoagulation groups regarding baseline characteristics. Propensity analysis showed a significant difference in sICH rate (0.0% vs. 14.8%, P = 0.044) in favor of LMWH. Independent outcome (mRS score 0–2) was achieved in a total of 31.0% and in 44.8% and 29.1% in the LMWH and UFH group, respectively ( P = 0.09). Propensity analysis showed a significant difference in the risk of ending up bedridden or dead (mRS score 5–6; 34.5% vs. 63.0%, P = 0.033) in favor of LMWH. Conclusions: Our study showed a lower rate of sICH and a shift towards improved outcome in thrombolysed patients with BAO treated with LMWH as compared with UFH.